THE INTEGRATION OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) WITH PEER TUTORING METHODS TO ENHANCE MOTIVATION AND ENGAGEMENT AMONG MANAGEMENT STUDENTS - Fitayanti, Sri; Husain, Dahlia; Alwolmabin, Zapira; Nirigu, Eides (English Review: Journal of English Education, 2024)
This study investigates the impact of integrating Mobile-Assisted Language Learning (MALL) applications with peer tutoring on student engagement, motivation, and learning outcomes in English language Teaching and learning. Utilizing a mixed-methods approach, the research involved pre- and post-intervention surveys, semi-structured interviews, and systematic observations. Quantitative data revealed significant improvements in students' engagement and motivation, with average scores increasing from 2.0 to 3.9 post-intervention. The standard deviation for engagement decreased from 0.7 to 0.5, indicating more consistent student responses. The qualitative analysis provided deeper insights, highlighting that students found MALL applications like Quizlet and YouTube particularly engaging and effective for learning. The thematic analysis of interviews underscored the benefits of peer tutoring in fostering a supportive learning environment, enhancing both collaborative and individual learning experiences. Excerpts from student interviews revealed increased interest and motivation, with students appreciating the flexibility and interactivity of the applications. These findings align with Vygotsky's theory of social constructivism, emphasizing the role of social interaction in learning. The study concludes that the integration of MALL with peer tutoring not only improves student engagement and motivation but also contributes to better language learning outcomes. This has important implications for educational practices and policies, suggesting that incorporating technology and collaborative learning strategies can enhance language education. Future research should explore long-term effects and scalability of such interventions.